The regulatory role of placental extracellular vesicle on trophoblast and endothelial cell functions - Bai, Kunfeng; Li, Xintong; Guo, Yanjie; Shang, Ye; Lin, Leqian; Chiu, Philip C. N.; Lee, Cheuk-Lun (Frontiers in Cell and Developmental Biology, 2025)
Extracellular vesicles (EVs) are cell-derived, membrane-bound vesicles that carry molecular cargo to facilitate communication between cells. During pregnancy, EVs are secreted by the syncytiotrophoblast layer of the placenta villi, where they mediate the functions of resident leukocytes and invading extravillous trophoblasts (EVTs) in the decidua. This study aims to isolate placental EVs (pEVs) from placental explant to examine their regulatory roles on EVT and endothelial cell functions. pEVs were successfully isolated from ex vivo cultured placental explant, which were capable to be internalized by EVTs and endothelial cells. pEVs stimulated the differentiation of trophoblast stem cells (TSCs) and enhanced the migration and invasion abilities of EVTs via CD147 receptor. Conversely, pEVs inhibited the tube formation ability and interleukin-6 (IL-6) secretion of endothelial cells. Together, these findings partially elucidate the role of pEVs during early pregnancy establishment, which may provide insights into pregnancy-related disorders.